Implementasi Pembiayaan Mudharabah di Bank Syariah Ditinjau dari Perspektif Ekonomi Islam - Iis Rizqi Amelia; Suprihatin . (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2013)
This study aims to determine the implementation of financing in islamic banks in the review from the perspective of Islamic economics. The method used was naturalistic qualitative methods. The data collection techniques are interviews, observation, documentation and triangulation are asking far financial marketing on the part of employees of PT. BSM KCP East Bekasi, how the implementation of financing in Islamic banks and whether the implementation of financing according to Islamic economics. The results of the study authors concluded that the implementation of BSM KCP financing in East Bekasi, there are 3 stages: First, financing plans were consistent with the al-Quran and al- Hadith and Fatwa of DSN NO: 07/DSN-MUI/IV/2000, kafalah as a complement to existing contract to guard the goal Second, the process of implementation of the contract-agreement under the terms of jurisprudence and accounting revenue recognition method using basic cash. Third, the results of the implementation that currently there is no problem in paying installments customers. Banks may have the customer because the customer financing principles mandate holders